EDUCATIONAL INCLUSION IN COLOMBIA: THEORIES, COMPETENCIES, AND APPLICABILITY. - Jeniffer Durán Pérez; Naysa Katerine Lobo Arévalo (LÍNEA IMAGINARIA, 2025)
The purpose of this scientific essay is to reflect on how contemporary education faces several challenges, one of the most significant being the existence of children and young people who are not integrated into formal education systems. This problem has generated the need to adopt a new vision in the field of education, focused on inclusion. However, it is important to note that there is also a lack of preparation among teaching staff to address this reality. The purpose of this document is to establish a relationship between the various aspects that characterize education, inclusion, and competencies, with the aim of promoting authentic inclusive education. Its purpose is to conduct a theoretical study of the current status of inclusive education, as well as the competencies acquired by university graduates in this specific field. This analysis is hermeneutical in nature. For its development, relevant theoretical aspects will be integrated, such as the historical evolution of education and its definition, as well as the concept of inclusive education, among others.